There are two solutions to the equations of Feynman’s Quantum Electrodynamics (QED): the newly discovered solution is free of quantum weirdness - Jeffrey H. Boyd, (JOURNAL OF ADVANCES IN PHYSICS, 2020)
No one previously noticed there is a second solution to the equations of Richard Feynman’s Quantum Electrodynamics (QED). It makes identical predictions in the lab. The new solution (Reverse-QED) is closer to nature: it is free of quantum weirdness. For example, it eliminates Schrödinger’s cat. This article is the first time the equations of R-QED have been published. The R-QED amplitude is the negative of Feynman’s amplitude. Because of the Born rule, both amplitude and negative amplitude, when squared, produce the same probability to be tested against empirical data. If you were to measure the distance from Los Angeles to New York City with R-QED’s accuracy, it would be exact to the breadth of a human hair. If reality corresponds to the newly discovered R-QED equations, but scientists use the old QED equations, the result would be predictions for the lab that are precisely accurate, but scientists would be unable to construct a coherent picture of the quantum world. R-QED is based on a different picture of how the quantum world is organized. Experiments, including a neutron interferometer experiment we review, show that particles follow waves backward. R-QED integrates in the same direction that the waves travel.